Comparative legal analysis of the categories of “abuse of rights” and “abuse of freedom of contract” (fraudulent transaction) - H. S. Hofeld (Bulletin of Kharkiv National University of Internal Affairs)
In the article, the author conducts a comparative legal analysis of the concepts of “abuse of rights” and “abuse of freedom of contract” within the context of fraudulent transactions in Ukraine. The study underscores the significance of examining transactions as one of the most intricate constructs in civil law theory and practice. In the contemporary era of societal digitalization and the ongoing development of democracy, there is an urgent need to establish effective mechanisms to facilitate the exercise of individuals’ subjective rights and obligations. Civil rights and obligations, including transactions, are an integral part of this process.